Analisis Biaya Pemboran Inpit Drill di Front X PT. ANTAM Tbk. Unit Bisnis Penambangan Nikel Sulawesi Tenggara - Najmi Hayati; Murad Murad (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. In the use of mineral or food resources for community welfare and the development of an area, a mining business is needed. For the mining business to run and make a profit, the potential of mineral resources or existing minerals must be known with certainty, as well as the existing risks, which can be specified as geological risks, economic-technological risks, and environmental risks, must be eliminated or at least minimized.At this time, PT. ANTAM Tbk. UBPN Southeast Sulawesi is carrying out stages, one of which is mining, namely detailed exploration or also called inpit drill drilling. This is very dependent on the nickel diarea that does not have the potential for high grade Ni from initial exploration results and determines whether inpit drill drilling activities are economical to do so that it is in accordance with the circumstances of the company that still maintains inpit drill activities despite initial exploration activities.Get the annual Cost Ratio value from inpit drill activities. Calculating the value of the benefits obtained from inpit drill activities carried out by PT. ANTAM Tbk. Southeast Sulawesi UBPN.Kata Kunci : Inpit drill, Top soil, Limonit, Saprolit, and Cost Ratio